Perancangan Website dan Media Promosi Online Sekolah Budaya Tunggulwulung - Fourine Ludyanto (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Sekolah Budaya Tunggulwulung (SBT) was established in 2014 for people who want to conserve local culture. However, since establishment this school still not capable to reach enthusiasts from youth, and below target student. Therefore, using websites and social media through Instagram and Facebook as an online promotional medium, it is expected to increase percentage youth followers for SBT. To concept online promotional planning, the writer use 4 stages designing method, ie data collection, data analysis using STP method (segmenting, targeting, and positioning), concepts design comprising 3 aspects (media planning, creative planning, and design planning), and visualization. The results of online promotional planning design is SBT’s website, and 12 social media designs for Instagram and Facebook content to inform netizen. With the existence of such media, Sekolah Budaya Tunggulwulung presence increase and more student wants to apply to SBT.